The Principal's Leadership Endevaor Improves Teacher Performance With An Emphasis On Teacher Well-Being - Miftah Faridli, Efi; Narimo, Sabar; Fauzati, Endang; Harsono, Harsono; Sutama, Sutama (International Journal of Educational Research & Social Sciences, 2024)
A dedicated and hardworking teacher consistently achieves better results in overcoming challenges and achieving educational goals. It is also important to consider ways to improve the effectiveness of education as well as teacher well-being in schools and educational institutions. The purpose of this study was to understand the role of teacher well-being as a mediating factor between principal leadership, and teacher commitment in relation to teacher performance. The population of this study was teachers of SMP Karasidenan Banyumas and the sample was collected using axial sampling techniques and open questionnaires and the sample used was 240 respondents. The findings of the study indicate that there is an influence of principal leadership, teacher commitment, and teacher well-being that have a positive and significant effect on teacher performance. In addition, principal leadership has a positive and significant effect on teacher well-being , but is different from the results of teacher commitment which has a negative but significant effect on teacher well-being . This study also shows that teacher well-being can be a mediating factor in the influence of principal leadership but is not significant, while teacher commitment itself has a negative and insignificant effect.